THE EFFECT OF CASH TURNOVER, RECEIVABLE TURNOVER AND TOTAL ASSET TURNOVER TO PROFITABILITY IN FOOD AND BEVERAGE COMPANIES LISTED ON THE IDX DURING THE 2018-2020 PERIOD - Wahyuningsih, Susanti; Widodo, Untung; Indriyatni, Lies; Yuliati, Yuliati (STIE Pelita Nusantara Semarang, 2023)
This study aims to determine the effect of Cash Turnover, Accounts Receivable Turnover and Total Asset Turnover on Profitability, either partially or simultaneously; The samples used in this study were 22 food and beverage companies listed on the IDX for the period 2018 – 2020. The data used is secondary data. While the method used is multiple linear regression method using the SPSS version 23 program, to obtain a comprehensive picture of the relationship between the independent variables and their dependent variables. The results of this study Cash Turnover has a positive and significant effect on profitability with t count > t tabal (2.662 > 1.979); Receivable turnover has no effect on profitability because t count < t table (-1.583 0.05; and Total Assets Turnover affects profitability, because t count > t table (3.600 > 1.979) with a significance of 0.000 F table (8.273 > 2.57) with a significance of 0.000.